Quasi-Contractive Mappings in Modular Metric Spaces - Yeol J. E. Cho; Reza Saadati; Ghadir Sadeghi (Journal of Applied Mathematics)
We prove the existence of fixed point and uniqueness of quasi-contractive mappings in modular metric spaces which was introduced by Ćirić